SPIRITUALITAS KEHENINGAN MARIA DALAM MATIUS 1:18-25 SEBAGAI KRITIK PROFETIS TERHADAP REAKTIVITAS KELUARGA DI ERA DIGITAL - Handri Ediktus; Oswaldus Abur (STIPAS Keuskupan Agung Kupang, 2026)
The phenomenon of digital reactivity has transformed family communication patterns into interactions that are fast, impulsive, and lacking in depth. This study aims to examine the spirituality of Mary's silence in Matthew 1:18–25 as a prophetic critique for families in the digital age. The research employs a library study with a narrative-critical exegetical approach, integrated with contextual hermeneutics. The findings suggest that Mary's narrative silence in Matthew 1:18–25 opens a theological reading of silence as an expression of faith subjectivity, inner sovereignty, and the capacity to postpone responses in order to make room for God's work. This spirituality of silence offers an ethical framework that helps families cultivate reflective communication and preserve relational depth within a digital culture that encourages instant responses. By actualizing the value of Mary's silence, families can safeguard relational integrity from the pressures of digital validation and strengthen their interior space for reflection.